2019
DOI: 10.1007/s10147-018-01385-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors associated with the therapeutic outcome of chemotherapy in very elderly cancer patients

Abstract: Background The purpose of this study was to detect background factors that might be associated with the therapeutic and curative outcome of chemotherapy in elderly cancer patients aged over 75 years. Methods A retrospective study was conducted for elderly cancer patients aged over 75 years who had received more than 2 courses of chemotherapy at our hospital. We analyzed the relationships between RECIST outcome and background factors, such as age, sex, clinical TNM stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…Meanwhile, factors other than polymorphism also play an important role related to chemotherapy response, such as tumor heterogeneity, age, comorbidity and severity, treatment modality, previous therapy response, stage, serum albumin levels, the general condition of patients on Zubrod and Karnofsky scales, histology, and types of cancer, as well as chemotherapy side effects that occur in patients. [104][105][106][107][108] Age is related to physiology and comorbidities. A study stated that patients under 60 years old had a higher chance of survival with p = 0.016.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, factors other than polymorphism also play an important role related to chemotherapy response, such as tumor heterogeneity, age, comorbidity and severity, treatment modality, previous therapy response, stage, serum albumin levels, the general condition of patients on Zubrod and Karnofsky scales, histology, and types of cancer, as well as chemotherapy side effects that occur in patients. [104][105][106][107][108] Age is related to physiology and comorbidities. A study stated that patients under 60 years old had a higher chance of survival with p = 0.016.…”
Section: Discussionmentioning
confidence: 99%
“…104 Meanwhile, research in Japan concluded that the level of serum albumin and patient comorbidity (Charlson Comorbidity Index) are fundamental factors in the clinical response of elderly patients over 75 years. 105 Other studies stated that comorbidity and their severity could affect the chemotherapy response. Studies conducted on breast cancer patients proved this with OR = 0.46; 95% (CI: 0.27--0.76) among patients with a Charlson score of 2 versus 0.…”
Section: Discussionmentioning
confidence: 99%
“…Ito et al [14] demonstrated that a CCI score of less than 2 points correlated with a favourable clinical outcome in cancer patients aged over 75 years. This was not reproduced in our younger aged cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Factors related to such adverse effects are roughly divided into therapy-related and patient-related 2 . While age, gender, performance status (PS), and chronic disease are obvious patient-related factors 3 , the oral environment is also thought to be associated with adverse effects 4 . Following the gut, the oral cavity houses the second most diverse and large microbiota including 700 species of bacteria, while the enormous amount of bacteria in dental plaque is equal to that found in stools 5 .…”
Section: Introductionmentioning
confidence: 99%